Prospective data collection and analysis of perforations and tears of latex surgical gloves during primary endoprosthetic surgeries - Zaatreh, Sarah; Enz, Andreas; Klinder, Annett; König, Tony; Mittelmeier, Lena; Kundt, Günther; Mittelmeier, Wolfram (German Medical Science GMS Publishing House, 2016)
Introduction: Surgical gloves are used to prevent contamination of the patient and the hospital staff with pathogens. The aim of this study was to examine the actual effectiveness of gloves by examining the damage (perforations, tears) to latex gloves during surgery in the case of primary hip and knee prosthesis implantation. Materials and methods: Latex surgical gloves used by surgeons for primary hip and knee replacement surgeries were collected directly after the surgery and tested using the watertightness test according to ISO EN 455-1:2000.Results: 540 gloves were collected from 104 surgeries. In 32.7% of surgeries at least one glove was damaged. Of all the gloves collected, 10.9% were damaged, mainly on the index finger. The size of the perforations ranged from ≤1 mm to over 5 mm. The surgeon's glove size was the only factor that significantly influenced the occurrence of glove damage. Surgeon training level, procedure duration, and the use of bone cement had no significant influence.Conclusions: Our results highlight the high failure rate of surgical gloves. This has acute implications for glove production, surgical practice, and hygiene guidelines. Further studies are needed to detect the surgical steps, surface structures, and instruments that pose an increased risk for glove damage.